Diagnostic Evaluation and Management of Acute Abdomen in Ayurveda A Conceptual Study - Haritha, A H; Balendra, Singh; Sweta, Singh; Kumar, Gopesh (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Acute abdomen is a condition which requires urgent attention and immediate treatment. The patient usually presents sudden onset of abdominal pain which is intolerable and also associated with other symptoms. In Ayurveda, the word Mahagada has been used for the lethality of the disease (in which there is fear of loss of life) and the word Atyayak has been used for emergency. Charaka Samhita and Susruta Samhita mentioned three such diseases under Ashta mahagada in which urgent or prompt treatment is asked and if the treatment is not done, death is certain. Material & method: Ayurvedic Samhitas, Modern books, and other manuscripts related with this topic are collected and a comparative study has been done. Result: Knowledge of acute abdomen is scattered in Ayurvedic Samhita. So, through this work we are trying to compile all the available details regarding the same and compare with modern science. Discussion: Ayurveda describes both conservative and surgical treatment options for acute abdomen. Acute abdomen can be managed extremely successfully with the use of Vedhana Nasaka, Sholaprasamana Maha Kashaya, Sophagna Maha Kashaya/Sopha Nasaka Oshadha (Anti-inflammatory Drugs), Agni deepana oushadha – deepaniya mahakashaya (Appetizers) etc.